MATERI PEMBELAJARAN PPKn BERBASIS NILAI LOKAL: IDENTIFIKASI DAN IMPLEMENTASI - winarno, Winarno (Universitas Muhammadiyah Ponorogo, 2018)
PPKn as moral education requires a set of values as learning materials as well as messages to be conveyed to learners. These values include Pancasila and the local values as a reflection of the heterogenity of the nation. The study aims to identify the local value of Javanese culture as material and how to implement it. The research method is descriptive with document analysis technique. The result was found any number of Javanese local values as the content of value education in PPKn. The Javanese local values are contained in moral norm and social norm. Value learning was done with a program approach by integrating local values in line with the humanitarian and social values of Pancasila into PPKn materials